Meningkatkan Kepercayaan Diri di Kelas dalam Membaca dan Menulis dengan Rapi di UPT SDN 060887 - Simangunsong, Geby Shabatini; Ritonga, Fajar Utama; Saragih, Mujahid Widian (Medan Resource Center, 2023)
The Field Work Practice (PKL) activities, which are integrated with the Campus Teaching Program of USU Cohort 2, span approximately 4 months and are conducted at the UPT SD Negeri 060887 Medan. Campus Teaching is an initiative that provides an opportunity for students to learn outside the classroom for a full semester. They become teacher partners and play a role in developing creative and innovative teaching strategies with a focus on improving student literacy skills. In its execution, I was responsible for classes 1 to 6, with a focus on literacy in reading for classes 1-3 and literacy in writing for classes 4-6. I adopted creative learning methods, including using electronic media to promote a culture of literacy. To assist students with limited learning interest, I applied an emotional approach, created a comfortable learning environment, integrated learning with play, and used music and poetry as engaging learning approaches. Additionally, breath control techniques were utilized to maintain the quality of learning when students felt fatigued.